1997
DOI: 10.1258/0956462971919219
|View full text |Cite
|
Sign up to set email alerts
|

Measuring outcomes in genitourinary medicine: involving service users in the measurement of outcomes

Abstract: Recently there has been increased emphasis on the user perspective in health care. At the same time the concern with effective health care is making us look more critically at the outcomes of treatment and other interventions, and the evidence available to us to make sense of effectiveness. This paper addresses the involvement of genitourinary medicine service users in outcome measurement through 3 linked questions: (1) What do we mean by outcomes? (2) What do we mean by users? and (3) What do we mean by invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies have revealed that minimizing mortality, symptom reduction, achieving successful discharge and patient satisfaction dominate the general professional conception of successful outcome. Patients are more inclined to emphasize reduction of symptoms, relieving pain, living independently, feeling positive and loss of stigma (Gann 1997, Repper 2000). As indicated, the health workers' main priority may be for patients to get well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have revealed that minimizing mortality, symptom reduction, achieving successful discharge and patient satisfaction dominate the general professional conception of successful outcome. Patients are more inclined to emphasize reduction of symptoms, relieving pain, living independently, feeling positive and loss of stigma (Gann 1997, Repper 2000). As indicated, the health workers' main priority may be for patients to get well.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients might not have the knowledge, language or motivation that user involvement requires. User preparation and training in assertiveness, confidence‐building, group work and knowledge of service organization are suggested as fundamental means to enhance a more active participative patient role (Bowl 1996, Gann 1997).…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Bob Gann's paper in particular, emphasized the need to re¯ect on the outcomes desired by users and how they might be involved in the measurement of outcomes in genitourinary medicine 8 . Similarly, Johnson argues that purchasers and providers view outcomes from very different perspectives, with purchasers focused on their local populations but providers usually viewing population outcomes from a wider multi-district or national perspective.…”
mentioning
confidence: 99%